Dose of Bicarbonate to Maintain Plasma pH During Maximal Ergometer Rowing and Consequence for Plasma Volume - Nielsen, Henning Bay; Volianitis, Stefanos; Secher, Niels H. (Frontiers in Physiology, 2022)
Rowing performance may be enhanced by attenuated metabolic acidosis following bicarbonate (BIC) supplementation. This study evaluated the dose of BIC needed to eliminate the decrease in plasma pH during maximal ergometer rowing and assessed the consequence for change in plasma volume. Six oarsmen performed “2,000-m” maximal ergometer rowing trials with BIC (1 M; 100–325 ml) and control (CON; the same volume of isotonic saline). During CON, pH decreased from 7.42 ± 0.01 to 7.17 ± 0.04 (mean and SD; p < 0.05), while during BIC, pH was maintained until the sixth minute where it dropped to 7.32 ± 0.08 and was thus higher than during CON (p < 0.05). The buffering effect of BIC on metabolic acidosis was dose dependent and 300–325 mmol required to maintain plasma pH. Compared to CON, BIC increased plasma sodium by 4 mmol/L, bicarbonate was maintained, and lactate increased to 25 ± 7 vs. 18 ± 3 mmol/L (p < 0.05). Plasma volume was estimated to decrease by 24 ± 4% in CON, while with BIC the estimate was by only 7 ± 6% (p < 0.05) and yet BIC had no significant effect on performance [median 6 min 27 s (range 6 min 09 s to 6 min 57 s) vs. 6 min 33 s (6 min 14 s to 6 min 55 s)]. Bicarbonate administration attenuates acidosis during maximal rowing in a dose-dependent manner and the reduction in plasma volume is attenuated with little consequence for performance.